Variáveis de proteção para burnout parental: uma investigação quali-quantitativa - Pedroso, Julia Dallasta (Universidade Federal de São Carlos, 2026)
Parental burnout is a condition of physical, mental, and emotional exhaustion associated with chronic stress related to parenting responsibilities. Factors such as low social support, coparenting conflicts, and underdeveloped socioemotional skills appear to contribute to its development. This study investigated the relationship between parental, coparental, and marital skills and symptoms of parental burnout, as well as the effects of programs and materials focused on parenting and coparenting. A total of 247 mothers and fathers who had or had not participated in programs or accessed materials on these topics took part in the study. Instruments assessing parental burnout, coparenting relationship, parenting styles, and marital social skills were administered. In addition, 40 participants completed semi-structured interviews about coparenting and parental well-being. The results showed that coparental support and expressiveness and empathy skills predicted lower parental burnout scores. In contrast, coparental conflict, inconsistent punishment, lax discipline, physical abuse, and, surprisingly, assertive conversational skills and proactive self-control predicted higher burnout scores. Differences were also observed in coparenting relationship quality, marital social skills, and parental burnout symptoms between parents who had or had not participated in interventions and accessed parenting-related materials. The interviews highlighted the importance of the coparenting relationship for parental well-being. Despite limitations related to the sample and the diversity of the analyzed programs, the findings suggest that interventions aimed at strengthening coparental, parental, and marital skills may act as protective factors against parental burnout.
Protective factors for parental burnout: a quali-quantitative study
Keywords: burnout parental; relação conjugal; parentalidade; relação coparental; CIENCIAS HUMANAS::PSICOLOGIA; 3. Saúde e Bem-Estar